STUDI EKSPLORATIF PERLINDUNGAN HUKUM TERHADAP KONSUMEN DAN TANGGUNG JAWAB PELAKU USAHA ATAS PENGGUNAAN BAHAN KIMIA FORMALIN PADA MAKANAN DI JAKARTA - Nainggolan, Anton (MAJALAH ILMIAH WIDYA, 2012)
The consuming foods produced or traded by the business is concerned with the consumerâs right to get the comfort, secure,and safety foods. The abuse of formaldehydes mechanicals into food is a violate at the interests of consumers. The purpose of thestudy is to show the business responsibility for losses consumers from consuming food formaldehyde and how the dispute settlementmechanism related consumer redress. This study used normative and empirical/Sociologist approach. The study showed that: (1)misuse of formaldehyde into food product is clearly contrary to the health. (2) The related business must responsible for the consumersâlosses from consuming food product that contains formaldehyde. Is is suggested that the goods or foods that are proven containingformalin should be withdrawn from circulation and destroyed